Religion in the recovery journey of individuals with experience of psychosis. Issue 4 (1st October 2016) - Heffernan, Suzanne; Neil, Sandra; Thomas, Yvonne; Weatherhead, Stephen
Abstract : This study investigated the role of religion in recovery from psychosis. Semi-structured interviews explored the experiences of ten participants. Data analysis was informed by social constructionist grounded theory. Several processes through which religion may influence recovery were identified: use of scriptures and rituals; a genuine connection with God; the struggle to maintain rituals; guidelines for living; choice and control; relating to others; enhancing psychological well-being; and making sense of experiences. Implications are that services should address religious needs in promoting recovery. This could be achieved through environmental adaptations, collaboration with religious representatives and incorporation of religion into psychotherapeutic approaches.